2015
DOI: 10.20396/sss.v10i1.1379
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdade de acesso entre diferentes etnias de pacientes com HIV/AIDS

Abstract: Dentre os vários objetivos estabelecidos no presente estudo, este em questão se refere a análise de acessibilidade da população negra em comparação com a população branca quanto à prevenção, diagnóstico e tratamento do HIV/AIDS e DST. Abrangem soropositivos masculinos e femininos, de etnia negra e branca, maiores de 18 anos, acompanhados no serviço de HIV/AIDS na UNICAMP. Utiliza entrevista semiestruturada. Resultados indicam desigualdade social entre negros e brancos: menor acesso a escolaridade, a renda e ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…10,[15][16] (To be continued) (Continuation) The data found in this study corroborate the current profile of the epidemic in Brazil and worldwide. If in the 80s almost all of the cases were male and occurred by homosexual transmission in contemporary society there is the prevalence among people with skin color "gray" and "black", 10,18 low-income, young people, low education and contaminated by heterossexual. 10,16 With regard to access, it was found that despite the reference service is located in Rio Grande do Norte capital; it also meets a large number of users residing outside the city of Natal.…”
Section: Discussionmentioning
confidence: 99%
“…10,[15][16] (To be continued) (Continuation) The data found in this study corroborate the current profile of the epidemic in Brazil and worldwide. If in the 80s almost all of the cases were male and occurred by homosexual transmission in contemporary society there is the prevalence among people with skin color "gray" and "black", 10,18 low-income, young people, low education and contaminated by heterossexual. 10,16 With regard to access, it was found that despite the reference service is located in Rio Grande do Norte capital; it also meets a large number of users residing outside the city of Natal.…”
Section: Discussionmentioning
confidence: 99%
“…Em se tratando do predomínio dos participantes do estudo ser de etnia branca, mesmo que a maioria da população brasileira com HIV/aids no Brasil e no mundo seja negra, Campos et al (2015) identificaram disparidade de acesso à assistência à saúde quando relacionada à etnia em consequência da desigualdade social entre brancos e negros quanto ao menor acesso a escolaridade, a renda e acessibilidade aos serviços de saúde pela população negra.…”
Section: Isolamento E Identificação Fenotípica Dos Microrganismosunclassified